IMPROVING MAGGOT CULTIVATION SKILLS TO ENHANCE FAMILY ECONOMY IN THE WOMEN FARMERS GROUP (KWT) BUNDA ATIRAH IN SURAU GADANG, NANGGALO DISTRICT, PADANG CITY - Renny Risdawati; Nursyahra Nursyahra; Ria Kasmeri; M. Sultan Akbar; Rahul Gazali; Siti Rosidah; Purnama Adinda Putri; Kholifah Kholifah (Universitas PGRI Sumatera Barat, 2024)
The Women Farmers Group (KWT) Bunda Atirah in Surau Gadang, Nanggalo District, Padang City, plays a significant role in enhancing family economy through various activities. This group has successfully engaged in hydroponic farming, poultry farming, and growing secondary crops. Additionally, KWT Bunda Atirah has taken steps to manage organic waste by cultivating maggots, which are used as an alternative feed in livestock and aquaculture. The demand for maggots as fish feed in Lake Maninjau reaches 2.5 tons per month, presenting an opportunity for KWT members. However, the lack of expertise and information has hindered the implementation of maggot cultivation. To address these challenges, a Community Partnership Program (PKM) with the assistance of lecturers from the Applied Biology and Biology Education Study Program of PGRI University Sumatera Barat (UPGRISBA) was initiated. The program involves providing maggot eggs, constructing maggot cages, and training KWT members in maggot cultivation. The training, attended by 23 KWT members, was well received and is expected to inspire the community to manage organic waste and generate income through maggot cultivation.